Pro- and anti-competitive provisions in the proposed European Union Data Act - Bertin Martens (Bruegel, 2023)
The proposed European Union Data Act gives users access and portability rights to the data generated by their use of tangible digital products and devices. This pro-competitive measure weakens the de-facto monopolistic control product manufacturers have over product data. However, the Data Act would also grant manufacturers a de-jure right to monopolistic pricing of data transfers to third-party service providers, restoring their control over data markets. Other anti-competitive provisions include restrictions on the use of data for competition purposes and a prohibition on transfering data to platforms identified as gatekeepers under the EU Digital Markets Act. Unnecessarily fuzzy definitions of products and data that fall under the Data Act would create uncertainty in implementation and incoherence with other EU data regulations. The Data Act should be simplified by dropping anti-competitive provisions and granting users and third-parties selected by users free access to all data generated by the use of a product or a service. This would increase competition in data-driven services and prevent users paying twice for their data. It would not disincentivise producers from investing in data-driven products and services. A further step could be the creation of a level playing field between producers and users in data-access rights. This can be achieved by introducing the principle of mutual exhaustion of data rights at point of sale. This would put all data co-generating parties in a position to generate economies of scale and scope in data aggregation, or data-driven externalities, to maximise innovation.
Keywords: 330